PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK BERBANTUAN GEOGEBRA CLASSROOM PADA MATERI PROGREM LINEAR UNTUK MENINGKATKAN KEMAMPUAN KOMUNIKASI MATEMATIS PESERTA DIDIK - Mita Sari Halawa (Jurnal Edukasi dan Penelitian Matematika, 2021)
The pupose of this research is to develop student worksheet Geogebra Classroom on the linear program is valid, practical and effective to improve student mathematical communication skills. Thi is because the student worksheet that used in the learning procces are still not able to facilitate students to be able to communicate their mathematical ideas. the type of thisresearch is Research and Development (R&D). This reseach used the plomp model which consist of three phases, namely preliminary reseach, development or prototyping phase, and assessment phase. The research data from the questionnaire were analyzed by using descriptive statistics, and the data from observation and interviews were analyzed by describtive techniques. The results of this research are (1) the student worksheets developed has a very valid category with a validity value of 89.02%, (2) the student worksheets can be used easily by students in the learning process with a practicality value of 90,14% with very practical category, (3) Geogebra Classroom assisted LKPD is effectively used in learning, this is seen from classical completeness, N-Gain Score test, and Effect Size test. where the result of classical completeness show more than 75% of students score are above the KKM, the N-Gain Score shows a value of 0,66 in the medium category, and effect size test scores 2,07 in the hidh category. Therefore, it can be said that the LKPD assisted by the Geogebra Classroom is effective in improving students mathematical communication skills .  Keywords – Student Worksheet, Mathemathic Communication Skill, Geogebra Classroom, Linear Program, Plomp.